How to create a mindful community of practice: exploring the social functions of group-based mindfulness practices facilitated via Zoom during COVID-19 - Tobias Mortlock, Jutta M.; Alapati, Hotri Himasri; Edginton, Trudi (Frontiers in Psychology, 2025)
This exploratory qualitative study was conducted to investigate the experiences of individuals who have been participating in online mindfulness sessions with an online mindfulness community since the beginning of COVID-19, i.e., during a period of heightened uncertainty and social isolation. The study’s purpose was to better understand the social functions of regularly practicing mindfulness in this online community of practice. Analyses from semi-structured interviews reveal how shared mindfulness practice may foster several pillars of connection and interbeing in this community of practice. These include improved mind–body awareness, coupled with a unique sense of trust and connection, which may have helped cultivate collective alignment and a sense of common humanity among research participants. Findings are discussed through the lens of interdependence theory, resulting in several exploratory propositions on how to create a mindful community of practice. The study concludes with a call for more research in this understudied research domain and invites mindfulness researchers and practitioners to test these propositions further. Its overall aim is to stimulate debate among individuals and groups intent on creating a mindful community in their workplace, educational setting, or neighborhood.